Analisis Faktor-Faktor Yang Memengaruhi Keputusan Pembelian Telur Ayam Ras Di Pasar Anyar, Kota Bogor - Doni Sahat Tua Manalu; Vela Rostwentivaivi; Putri Pebrianti Utami; Nadira Marsandri Ratnakaniya; Azryl Gustian Azhar; Almalia Pramena; Aulia Mardatila (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This research aims to analyze the factors that influence the decision to purchase purebred chicken eggs at Pasar Anyar, Bogor City, with a focus on age, distance, income, price of purebred chicken eggs, education and employment. The method used is a survey using a questionnaire as a tool for collecting primary data. The research sample consisted of 80 consumers who bought purebred chicken eggs at Pasar Anyar, Bogor City. The results of multiple linear regression analysis show that only distance, income and price significantly influence consumer behavior in purchasing purebred chicken eggs, where for every 1 unit increase in distance, the purchase of purebred chicken eggs decreases on average by 0.289%, for every increase in income. by 1 unit, the purchase of purebred chicken eggs increases by an average of 0.902%, and for every 1 unit price increase, the purchase of purebred chicken eggs decreases by an average of 13.710%. Other factors such as age, education, and employment did not have a significant impact. This emphasizes the important role of distance, income, price in shaping consumer decisions. This study provides insight for the purebred chicken egg industry to design more effective marketing strategies, by segmenting the market based on distance, income and price.